Penggunaan Catalytic Converter dari Bahan Kuningan dengan Ketebalan 0,2 mm Terhadap Emisi Gas Buang Kendaraan Pada Motor 2 Tak - Muhammad Fahrurrozi; Imam Prasetyo (Politeknik Negeri Cilacap, 2020)
In reducing the remaining harmful exhaust emissions of motorcycles, one of them is by improving the quality of fuel and vehicle technology so that the combustion becomes better and more optimal, then the second way is to process exhaust gas through an exhaust emission controller. Catalytic Converter is a device that is installed in the exhaust channel of vehicle which has function to reduce the residual emissions from motorized combustion gases. The purpose of this study was to determine the effect of using a catalytic converter made of brass with a thickness of 0.2 mm to reduce levels of CO and HC in motorized vehicles. Tests were carried out by using a gas analyzer to determine the value of CO and HC concentrations. The exhaust emission test is carried out in two stages, the exhaust emission test with a standard exhaust and exhaust gas emission test with a catalytic converter with the variations of engine speed of 1500 rpm, 2000 rpm, 2500 rpm, 3000 rpm, 3500 rpm, 4000 rpm. From the research results, it was found that the effect of using a catalytic converter made of brass with a thickness of 0.2 mm with a fin model the most effective decreased on exhaust emission levels was at 1500 rpm, the CO value decreased by 1.82% from 3.96% to 2.14%. and HC value fell 4,412 ppm from 9,999 ppm down to 5,587 ppm.